Correlation between participation in physical activity and healthy nutrition: An example of a sports science faculty - YASEMIN ARI; ERGUN CAKIR (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: It is important to encourage people to participate in physical activities and to develop motivational approaches to healthy nutrition in order to maintain a healthy life. This study was conducted to examine the relationship between the physical activity levels of university students and their attitudes to healthy nutrition. Material and methods: 392 (153 female and 239 male) university students voluntarily participated in the study. In the study, the International Physical Activity Questionnaire-Short Form (IPAQ-SF) and the Attitude Scale for Healthy Nutrition (ASHN) were used. Results: As a result of the analysis conducted in the study group, in the comparison of the students studying at the sports sciences department in terms of gender, smoking and regular exercise variables, a statistically significant difference was found in the level of participation in physical activity in the variable of meals consumed during the day. A positive significant relationship was found between the participants' attitude towards healthy nutrition and their level of participation in physical activity. Conclusions: It was determined that students with high participation in physical activity also have high attitudes towards healthy nutrition.